An unusual age presentation of mature cystic teratoma: a case report - Inkollu, Sindhura; Nelavelli, Ashwini; Merugu, Shyam Mohan Rao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Mature cystic teratoma compromise 20-30% of all ovarian tumours. They are mostly seen in patients between 20 and 40 years of age and are mostly asymptomatic. Malignancy incidence is high in postmenopausal group. Here, we report a case of mature cystic teratoma presenting unusually in a 65 year old postmenopausal woman with pain abdomen. A 65 year old postmenopausal woman presented with lower abdominal pain of 15 days duration. Upon examination, a mass of size 7×8 cm felt on bimanual examination. CT showed the same cyst that has a focal enhancing mural nodule with fat density in it. Total abdominal hysterectomy with bilateral salpingo oopherectomy done. Histopathological examination confirmed mature cystic teratoma. Although mature cystic teratoma is rare after 40 years age, especially in postmenopausal women and are usually malignant in that age group, it can have an unusual age presentation at 65 years with benign nature as in our case.